A Critical Discourse Analysis dalam Kajian Tafsir Alquran: Studi Tafsir Al-Azhar Karya Hamka - Munawan, M. (Research and Development Institution, Darussalam Institute for Islamic Studies, 2018)
One of the phenomenal Tafsir in Indonesia written by non-Arabic commentators is Tafsir Al-Azhar by Hamka (Haji Abdul Malik Karim Amrullah). This interpretation becomes a reference for Muslims in Indonesia before other modern interpretations come. This interpretation is widely referenced by Qur’an scholars because the language is easy to digest and detailed explanation in accordance with present times. Based on a search of some literature there is no specific discussion about manhaj Tafsir Al-Azhar and its application. So this article will critically examine Hamka’s Tafsir Al-Azhar, especially from the aspect of manhaj and its application in its interpretation. Specifically this article will discuss the method of interpretation, the mechanism of interpretation, and the style of interpretation. The approach used by the writer is Norman Fairclough’s critical discourse analysis. Critical discourse analysis is one of the methods of analyzing discourse in a work by critically analyzing. Fairclough uses discourse analysis by pointing the use of language as a social practice not just an individual activity. In addition, Fairclough also created a model that brought together discourse analysis which was based on linguistics as well as on socio-political thought, or generally integrated with social change. The results of the study shows that Tafsir Al-Azhar is included in the category of non-school interpretation (non-madzhab), which is also characterized by patterns of thought and modern interpretation, especially from Tafsir Al-Manâr and Fî Zhilâl Al-Qur'ân, two books of tafsir are more patterned of adabi -ijtima’î.